Catalpol Protects Against High Glucose-Induced Bone Loss by Regulating Osteoblast Function - Zhao, Lu; Du, Wei; Zhao, Dandan; Ji, Xueyan; Huang, Yanfei; Pang, Yong; Guo, Kaijin; Yin, Xiaoxing (Frontiers in Pharmacology, 2021)
Objective: The overall objective of this study was to investigate the effects of catalpol on bone remodeling of diabetic osteoporosis by regulating osteoblast differentiation and migration. Method: Using a murine model of diabetic osteoporosis, to detecte the protective effects of catalpol on bone loss, architectural deterioration of trabecular bone and bone metabolism biomarkers were tested. A model of MC3T3-E1 cells was established by treatment with high glucose, the regulatory role of catalpol in the differentiation and migration were tested by western blot, ALP staining and Alizarin Red staining. Results: Catalpol treatment markedly ameliorated trabecular bone deterioration by reducing degenerative changes of trabecular structure by improving the bone formation marker levels of ALP, osteopontin, type I collagen and osteocalcin, as well as the level of OPG/RANKL. Catalpol enhanced cell motility and scattering following gap formation of MC3T3-E1 cells. Conclusion: The results indicated that catalpol exhibits a protective effect against diabetic osteoporosis by regulating the differentiation and migration of osteoblast.